MUSICAL THINKING: DEFINITION, STRUCTURE, AND COGNITIVE FEATURES - Akramjon Nazarov (Modern American Journals, 2025)
This article examines the concept and essence of musical thinking as a distinct form of artistic and cognitive activity. It explores theoretical perspectives on the emergence of musical art and its integral role in shaping human perception, emotion, and imagination. The study analyzes how musical thought operates through sound structures, rhythm, and texture, forming an expressive system that bridges sensory experience and intellectual reflection. Special attention is given to stylistic phenomena such as homophony and glissando, which illustrate the dynamic interaction of melodic and harmonic layers within musical texture. The paper also discusses the impact of mass culture on the transformation of musical consciousness in contemporary society, emphasizing the need to preserve aesthetic values and creative depth amid technological and cultural change.
Keywords: Musical thinking, homophony, glissando, rhythm, texture, mass culture.